Development of an anti-crisis program of the enterprise on the basis of digital marketing - Oborina, Anastasiia (National Technical University "Kharkiv Polytechnic Institute", 2024)
Since 2019 the World have witnessed significant changes, not only within Ukraine but globally, notably the impact of the COVID-19 pandemic. Some of these effects continue to persist even after four years. For Ukraine, the situation has been particularly challenging, exacerbated by a two-year fullscale invasion that has posed unprecedented challenges for small and mediumsized businesses. Despite these challenges, Ukrainian entrepreneurs are showcasing resilience and adaptability to conditions of immense uncertainty. The relevance of digital marketing in the development of anti-crisis programs for businesses remains poorly understood. Initial investigations into this field, however, do not provide a comprehensive view of the problem. Therefore, further research is essential to directly address the development of anti-crisis programs at enterprises that can navigate these challenging circumstances successfully. The study aims at comprehensive strategic management of enterprises during crises and the exploration of innovative marketing methods for economic savings and development.
Keywords: digital marketing; anti-crisis programs; innovative marketing methods; internet marketing